Peran Kepemimpinan Transformasional dalam Pengembangan Organisasi untuk Meningkatkan Mutu Pendidikan (Studi Kasus Sekolah Alam Indonesia) - Tri Puji Hindarsih; Sita Ratnaningsih (Al-Munawwarah : Jurnal Pendidikan Islam, 2025)
This research aims to gain a thorough understanding of how transformational leadership propels organizational growth and raises educational standards at Sekolah Alam Indonesia. This study examines the leadership behaviors of unit leaders, including headmasters and principals, in creating a learning organizational culture at different educational levels using a qualitative methodology and a case study design. According to the results, transformational leadership traits like intellectual stimulation, individual empowerment, and shared values greatly enhance teacher involvement, create reflective spaces, and spur innovations in the educational process of students. However, organizational dynamics still face various structural challenges, including the absence of a solid cross-unit coordination system, managerial capacity gaps among leaders, and the absence of a monitoring mechanism that can map the organization's development comprehensively. These conditions mean that the transformation that has occurred is not fully systemic and still relies on the figurative power of individual leaders. The results of this study contribute to the discourse on values-based and community-based alternative education management, by highlighting the importance of institutionalizing an adaptive leadership system oriented towards collective learning. In the context of Sekolah Alam Indonesia, which has a humanistic and ecological vision, transformational leadership is not only a managerial tool, but also a strategic foundation in shaping the character of an organization capable of sustainable growth, learning, and adaptation.